Halal-Friendly Experiences in Hotel: A Systematic Literature Review - Fikriyah, Aria; Hidayat, Kadarisman; Kusumawati, Andriani (Sekolah Pascasarjana Universitas Brawijaya, 2025)
This study presents a systematic literature review aimed at identifying the key factors influencing customer loyalty, with a particular focus on the role of ethical behavior, relational benefits, and customer satisfaction. Utilizing the PRISMA framework, a comprehensive search was conducted across multiple online databases, resulting in the selection and analysis of 57 relevant articles. The review synthesizes existing empirical evidence to examine how ethical practices—particularly in the banking sector—contribute to building long-term customer relationships. The findings reveal that ethical behavior significantly enhances customer satisfaction, which in turn strengthens trust and commitment, ultimately leading to increased customer loyalty. Relational benefits, such as confidence, social bonds, and special treatment, were also identified as mediating factors that enhance customer retention and encourage positive word-of-mouth. The study highlights the importance of aligning business practices with ethical standards to foster sustainable competitive advantage, particularly in service-oriented industries like banking. Drawing from Stimulus-Organism-Response (SOR) theory, the conceptual framework proposed in this paper illustrates the psychological process through which ethical stimuli influence internal customer states and subsequent behavioral responses. This review contributes to both academic knowledge and managerial practice by offering a structured understanding of the mechanisms underlying customer loyalty. It also identifies gaps in current research and suggests directions for future studies, particularly in expanding the scope beyond the banking sector and developing more nuanced models of ethical influence in customer relationships. Keywords: halal-friendly experiences, hotel, hospitality, tourist loyalty, literature review